UJI EFEKTIVITAS EKSTRAK BIJI BENGKUANG (Pachyrizus erosus (L.) Urban) SEBAGAI INSEKTISIDA NABATI TERHADAP MORTALITAS KUTU BERAS (Sitophilus oryzae) (Journal of Health, Technology and Science (JHTS), 2020)
Jicama seeds contain rotenone which is a poisonous isoflavonoid as a broad-spectrum insecticide and has an influence on insect mortality.This study aims to know the effectiveness of Jicama Seed Extract and the effective concentration of Jicama Seed extract as a vegetable insecticide to-wards the mortality of rice lice. The jicama seed extract was divided into 5 treatments with one control namely 1.00%, 5.00%, 10.00% and 15,00% with each one three repetitions.The results of the study were analyzed using parametric prerequisite tests. The normality test is used Kolmogorov-Smirnov, and Homogeneity test used Levene's test. For hypothesis 1 analyzed using the F-test (One Way ANOVA) then hypothesis 2 is analyzed using the Duncan test.The results of the study showed there is an influence of Jicama seed extract (Pachyrizus erosus (L.) Urban) as a vegetable insecticide towards the mortality of rice lice (Sitophilus oryzae) which is indicated by the value of sig. amounting to 0.00
Keywords: Jicama Seed, Vegetable Insecticide, Mortality, Rice Lice